2012
DOI: 10.1007/s11670-012-0029-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphism associations for colorectal cancer in southern Chinese population

Abstract: Objective: Genome-wide association studies (GWAS) have identified 11 loci that influence the risk of developing colorectal cancer (CRC). Given that these studies were conducted in European Caucasian populations, it is not clear whether the results are relevant for populations with different ethnicities. The aim of this study was to examine these associations in a southern Chinese population.Methods: Eleven single-nucleotide polymorphisms (SNPs), rs12701937, rs16892766, rs7014346, rs6983267, rs719725, rs1079566… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The SNP rs4444235, which is located 9.4 kb upstream of the gene encoding bone morphogenetic protein 4 (BMP4), was previously associated with CRC and gastric cancer risk [22,23] . Although the CT genotype showed a protective effect against gastric cancer [23] , it was also associated with an increased CRC risk [24] . This SNP has been proposed to act as a cis-regulator of BMP4 and thus confer a risk for CRC [25,26] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNP rs4444235, which is located 9.4 kb upstream of the gene encoding bone morphogenetic protein 4 (BMP4), was previously associated with CRC and gastric cancer risk [22,23] . Although the CT genotype showed a protective effect against gastric cancer [23] , it was also associated with an increased CRC risk [24] . This SNP has been proposed to act as a cis-regulator of BMP4 and thus confer a risk for CRC [25,26] .…”
Section: Discussionmentioning
confidence: 99%
“…This association was not strongly modified by sex, body mass index, alcohol, smoking, aspirin or various dietary factors [20] . The SNP rs4444235, which is located 9.4 kb upstream of the gene encoding bone morphogenetic protein 4 (BMP4), was previously associated with CRC and gastric cancer risk [22,23] . Although the CT genotype showed a protective effect against gastric cancer [23] , it was also associated with an increased CRC risk [24] .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 15 eligible studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in the meta-analysis involving 58,626 cases and 88,098 controls. The literature selection process was showed in supplementary Fig.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…In order to investigate whether rs10411210 polymorphism is associated with CRC risk, GWAS and candidate studies are conducted in European, Asian and American populations [9][10][11][12][13][14][15][16][17]. However these studies reported consistent and inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported significant association between rs10411210 and CRC (P < 0.05) [17], and the other studies reported no association between rs10411210 and CRC (P ! 0.05) [9][10][11][12][13][14][15][16]. Kang et al recently examined the relationship between 22 GWAS-identified single nucleotide polymorphisms (SNPs) and the clinical outcomes of CRC patients [18].…”
Section: Introductionmentioning
confidence: 99%